PHYLOGENETIC RELATIONSHIPS WITHIN APIALES: EVIDENCE FROM WOOD ANATOMY - OSKOLSKI, A. A. (Edinburgh Journal of Botany, 2001)
Wood anatomical data confirm the close relationships of most Araliaceae to Apiaceae, but do not indicate any intermediate groups between the two families. Heteromorpha Cham. & Schltdl., Bupleurum L. and Melanoselinum Hoffm. form a well-delimited group distinguished from other woody Apiaceae by helical thickenings on their vessel walls, septate fibres, and mostly homogeneous rays. The woodiness in Nirarathamnos Balf.f. and Myrrhidendron J. M. Coult. & Rose is likely to be of secondary origin.
Keywords: Apiaceae; Araliaceae; systematic wood anatomy